2008
DOI: 10.1093/occmed/kqm156
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health in the Andalusian Fisheries Sector

Abstract: Fishery workers had a high prevalence of self-reported medical problems, a high prevalence of self-medication, poor diets and frequently smoked. Self-medication and some medical conditions (diabetes, angina and depression) may reflect a potential failing of health checks and pre-employment checks. National health services and insurance companies dealing with occupational health should focus more on appropriate health checks, illness prevention and health promotion activities for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 8 publications
(8 reference statements)
3
35
1
2
Order By: Relevance
“…Percin et al [17] and Novalbos et al [22] only achieved questionnaire response rates of 20% and about 3%, respectively in ports in the Aegean Sea and Andalusia, Spain. The variance in response rate can be caused by multiple factors, and a study of Ruyter et al 2004 [23] suggests that short surveys achieve higher response rates than longer questionnaires.…”
Section: Discussionmentioning
confidence: 97%
“…Percin et al [17] and Novalbos et al [22] only achieved questionnaire response rates of 20% and about 3%, respectively in ports in the Aegean Sea and Andalusia, Spain. The variance in response rate can be caused by multiple factors, and a study of Ruyter et al 2004 [23] suggests that short surveys achieve higher response rates than longer questionnaires.…”
Section: Discussionmentioning
confidence: 97%
“…81% of fishermen smoked on board, two thirds smoking more than 20 a day and 72% smoking more often on board than ashore [27]. Novalbos et al [22] found that 9% of fishers used illegal drugs, of whom 3% used drugs on board. 30% of fishermen drank alcohol on board, at an average of 8.5 g/day.…”
Section: Drug Use On Boardmentioning
confidence: 99%
“…Sixteen articles studying addictions amongst seafarers were selected: 15 cross-sectional descriptive studies and 1 cohort study (Table 1) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Two studies measured urinary markers [13,14].…”
Section: Selected Articlesmentioning
confidence: 99%
“…Smoking prevalence varies greatly between studies in others countries; yet it is strong enough ranging from 37% to 72% [38][39][40][41]. Over 80% of Scottish fishermen reported drinking alcohol [42] and 45% of Greek seamen had daily consumption of wine [43]; in our study, French fishermen were 89.5%.…”
Section: Comparison With Other Studies In Seamen Populationmentioning
confidence: 60%